Unsteady Diffusive Mass Transfer in a Follicle Modelled as an Annular Region - Jagadeesha, S.; Ramarao, Indira; Madhura, K.; Sreegowrav, K. R. (Communications in Mathematics and Applications, 2023)
Oxygen supply in a follicle is modelled using the species transport equation. The follicle is modelled as an annular region formed by concentric circles where the inner circle represents the granulosa layer fluid and cells. Concentration is obtained analytically and graphically depicted. Oxygen transport in the outer follicle region remains constant with time and increases in the antrum layer from a very low value and reaches a constant value close to that of the outer region.